Missionary Ethics in Q 10:2−12 - Roth, Dieter T. (HTS teologiese studies, 2012)
Elements of the mission discourse of the Synoptic Gospels are found in Mark 6:6b−13; Matthew 9:35−10:15; Luke 9:1−6 and Luke 10:1−20. Similarities and differences in these accounts have led many New Testament scholars to posit the presence of a mission discourse in Q. This discourse, along with the parable that introduces it (Q 10:2), provides insight into how Q conceives of ‘mission’ as well as the ethical principles and precepts that are part of Jesus’ missional charge in this document. Through an intertextual approach to Q, with particular emphasis on narrative structure and imagery, this paper considered the interplay of mission and ethics in this early Christian text.